Watermarking Image Depending on Mojette Transform for Hiding Information - Majeed Zangana, Hewa (International Journal of Computer Sciences and Engineering, 2020)
This paper describes a new image watermarking method for which is suitable for both copyright protection and information hiding. The presented method is based upon the morphological mathematics properties of the Mojette Transform [1,2] and the Mojette Phantoms[3]. The main properties of the Mojette transform are briefly introduced and the concept of linked phantoms which depicts the null space of the operator is presented. In this paper the Mojette Phantoms can be used not only as the embedded watermark, but also can be used as the mark which is inscribed with some certain information, e.g. Chinese characters. Corresponding embedding and extractions of either the mark or the hidden message are then described. Finally, experimental results are presented in the last section.